Photopatch Testing in New Zealand: A 12-Year Retrospective Review. Issue 1 (January 2021) - Kim, Yena; Patel, Denesh C.; Greig, Deborah; Cheng, Harriet
Abstract : Background: Little is known about the common photoallergens in New Zealand, where ultraviolet exposure is particularly high. Availability of photopatch testing is limited because of it being performed in very few tertiary referral and contact dermatitis clinics. Objective: To review the photopatch testing experience in New Zealand. Method: A retrospective review of all patients who underwent photopatch testing at a tertiary referral center in Auckland from 2008 to 2019 was performed. Results: Seventy patients had photopatch testing over the 12-year period. Of the 58 patients tested using the photoallergen series, 6 (10%) patients had a positive photopatch test reaction, of which 4 were to promethazine and 2 were to benzophenone-3. The most common postpatch diagnosis was endogenous dermatitis (54%), followed by allergic contact dermatitis (21%), photoallergic contact dermatitis (9%), and chronic actinic dermatitis (4%). Conclusions: Both patch and photopatch testing are important investigations in patients with suspected photoallergic contact dermatitis. Promethazine and benzophenone-3 were the most frequent and only photoallergens in our population. Promethazine sensitization was via oral exposure, supporting a mechanism of systematized photoallergy to promethazine. Abstract : Supplemental digital content is available in the text.